Protective effect of Saccharomyces boulardii on intestinal mucosal barrier of dextran sodium sulfate-induced colitis in mice - Jin-Pei Dong; Yue Zheng; Ting Wu; Qun He; Gui-Gen Teng; Hua-Hong Wang; Li-Shao Guo (Chinese Medical Journal, 2019)
Abstract. Background:. The effect and mechanism of Saccharomyces boulardii (Sb) in inflammatory bowel disease are unclear. The objective of the study was to evaluate the impact of Sb on intestinal mucosal barrier and intestinal flora in a colitis mouse model. Methods:. Forty C57BL/6J male mice were randomly assigned to five groups: normal control group (A), pathologic control group (B), Sb treatment group (C), mesalazine treatment group (D), and Sb combined with mesalazine treatment group (E). Colitis was induced by the addition of 2.5% (wt/vol) dextran sodium sulfate (DSS) in the drinking water ad libitum for 7 days. The general condition, weight change, stool property, and bloody stool level of mice were observed to evaluate the disease activity index. The expression of zona occludens-1 (ZO-1) and occludin in intestinal tissue were measured by immunohistochemistry. The level of tumor necrosis factor-α (TNF-α) and interleukin (IL)-8 in plasma was measured by enzyme linked immunosorbent assay. Inter-cellular tight junctions were observed by transmission electron microscopy. The feces and intestinal contents were collected sterilely, and intestinal flora was analyzed by 16S rRNA sequencing. Results:. Compared with group B, Sb reduced the disease activity index and histological score of group C (disease activity index: group B 2.708 ± 0.628, group C 1.542 ± 0.616, PBC = 0.005; histological score: group B 9.875 ± 3.271, group C 4.750 ± 1.832, PBC = 0.005) in DSS-induced colitis in mice. Sb exerted a protect effect on the expression of ZO-1 (group B 2.075 ± 1.176, group C 4.225 ± 1.316, PBC = 0.019) and occludin (group B 2.200 ± 0.968, group C 3.525 ± 1.047, PBC = 0.023). Compared with group B, Sb decreased the level of TNF-α and IL-8 of group C (TNF-α: group B 716.323 ± 44.691 ng/L, group C 521.740 ± 90.121 ng/L, PBC = 0.001; IL-8: group B 128.992 ± 11.475 pg/mL, group C 106.283 ± 15.906 pg/mL, PBC = 0.012). Treatment with Sb preserved the tight junctions and ameliorated microvilli and inter-cellular space. Treatment with Sb also showed its own characteristics: a higher percentage of Bacteroidetes and a lower percentage of Firmicutes, with significant differences or a significant trend. The proportion of the S24-7 family was increased significantly in the Sb treatment group. Conclusions:. Sb shows an anti-inflammatory effect and has a protective effect on the intestinal mucosal mechanical barrier. Sb may up-regulate the abundance of family S24-7 specifically, and maybe a mechanism underlying its function.